Two-loop amplitudes for O α s 2 $$ \mathcal{O}\left(α_s^2\right) $$ corrections to Wγγ production at the LHC - Simon Badger; Heribertus Bayu Hartanto; Zihao Wu; Yang Zhang; Simone Zoia (Journal of High Energy Physics)
Abstract We present the two-loop helicity amplitudes contributing to the next-to-next-to-leading order QCD predictions for W-boson production in association with two photons at the Large Hadron Collider. We derived compact analytic expressions for the two-loop amplitudes in the leading colour limit, and provide numerical results for the subleading colour contributions. We employ a compact system of integration-by-part identities provided by the NeatIBP package, allowing for an efficient computation of the rational coefficients of the scattering amplitudes over finite fields.